Wnt1 Accelerates an Ex Vivo Expansion of Human Cord Blood CD34+CD38− Cells - Kamonnaree Chotinantakul; Patcharee Prasajak; Wilairat Leeanansaksiri (Stem Cells International)
Cord blood hematopoietic stem cells (CB-HSCs) transplantation has been increasing gradually with facing the limitation of insufficient quantity of HSCs in each CB unit. Therefore, efficient expansion methods which can maintain stem cell characteristics are needed. In this study, umbilical CB-CD34+ cells were cultured in two different cytokine cocktails: 4 factors (4F = Flt3-L, SCF, IL-6, and TPO) and 5 factors (5F = Wnt1 + 4F) in both serum and serum-free media. The data revealed that the best condition to accelerate an expansion of CD34+CD38− cells was serum-free culture condition supplemented with 5F (5F KSR). This condition yielded 24.3 ± 2.1 folds increase of CD34+CD38− cells. The expanded cells exhibited CD34+ CD38− CD133+ CD71low CD33low CD3− CD19− markers, expressed nanog, oct3/4, c-myc, and sox2 genes, and maintained differentiation potential into lymphoid, erythroid and myeloid lineages. The achievement of CD34+CD38− cells expansion may overcome an insufficient quantity of the cells leading to the improvement of the stem cell transplantation. Altogether, our findings highlight the role of Wnt1 and the new culture condition in stimulating hematopoietic stem/progenitor cells expansion which may offer a new therapeutic avenue for cord blood transplantation, regenerative medicine, stem cell bank applications, and other clinical applications in the future.